Dicer-dependent pathway contribute to the osteogenesis mediated by regulation of Runx2 - Zhou, Jie (Am J Transl Res, 2016)
Osteogenesis is mediated by sophisticated interactions of various molecular functions and biological processes, including post-transcriptional regulation. A range of miRNAs have been reported to regulate bone homeostasis and osteoblasts differentiation either positively or negatively through multiple signaling pathways. RNase III endonuclease Dicer is the key enzyme required for the biogenesis of miRNAs and small interfering RNAs. To determine the global influence of miRNAs on regulation of osteogenesis of pre-osteoblast cells, the transcriptional regulation of Dicer and the function of Dicer during osteoblast differentiation and mineralization were investigated. Runx2 binding directly to the Dicer promoter region was characterized in MC3T3-E1 cells by chromatin immunoprecipitation (ChIP) and luciferase promoter reporter assays. Overexpression or knockdown of Runx2 resulted in increase or decrease of Dicer expression, respectively. Furthermore, abatement of Dicer in MC3T3-E1 cells down-regulated the expression of osteogenic marker genes and mineralization ability, at least partly involving Dicer-dependent processing of the miR-21a-5p targeting PTEN via pAKT/pGSK3β/β-catenin signaling pathways. Taken together, the study demonstrates the role of Dicer in osteogenesis and suggests that Dicer is required, in part, for Runx2 regulation of osteoblast differentiation.